Islamizing the "feminine, feminist and female" voices in three Malaysian short stories by Anglophone women writers - Abdul Manaf, Nor Faridah (IIUM Press, 2000)
There has been a great concern among Muslim teachers of English on the need to study English literary texts from the Islamic perspectives. But how does one Islamize literary texts written in English by non-Muslims? Will this not be another hegemony of one ideology over the other? There also are concerns among Muslim scholars about the position of Western literary criticisms among which is feminism, which is seen as a Western import, out to corrupt the Muslim world. What is clear here is the existence of distrust of one cultural force against the other. This paper claims to explore the impact of creative encounters between Islamic criticism and feminism. The Islamic reading of English literary texts (Malaysian Islamizing the "feminine, feminist and female" voices in three Malaysian short stories by Anglophone women writers women's writing) serves as a model to deconstruct meanings in the texts to suit local sensibility and sensitivity. It is also to dispel the popular believe that Islam will clash with any ideology and civilisation.